2013
DOI: 10.1002/anie.201210077
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Metal–Oxide Interface in Catalysis: In Situ Studies of the Water–Gas Shift Reaction by Ambient‐Pressure X‐ray Photoelectron Spectroscopy

Abstract: Where oxide and metals meet: The activation of an efficient associative mechanistic pathway for the water-gas shift reaction by an oxide-metal interface leads to an increase in the catalytic activity of nanoparticles of ceria deposited on Cu(111) or Au(111) by more than an order of magnitude (see graph). In situ experiments demonstrated that a carboxy species formed at the metal-oxide interface is the critical intermediate in the reaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
284
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 300 publications
(301 citation statements)
references
References 36 publications
17
284
0
Order By: Relevance
“…After adding another 200 mTorr of H2O into the reaction to make a ~5:1 (H2O/EtOH) vapor mixture, deconvolution of the spectrum shows an extra gas phase feature at 536.0 eV for 200 mTorr water vapor. [32][33] Moreover, the peak intensity of the ceria lattice O is significantly attenuated, which is mainly a result of the increased scattering of photoelectron due to the higher concentration of gas as well as surface adsorbed species between the ceria film and analyzer cone. The catalyst was then heated from 300 to 700 K by 100 K increments in an ambient of 40 mTorr ethanol and 200 mTorr H2O, and the corresponding AP-XPS results for the C 1s, O 1s and Ce 4d regions are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…After adding another 200 mTorr of H2O into the reaction to make a ~5:1 (H2O/EtOH) vapor mixture, deconvolution of the spectrum shows an extra gas phase feature at 536.0 eV for 200 mTorr water vapor. [32][33] Moreover, the peak intensity of the ceria lattice O is significantly attenuated, which is mainly a result of the increased scattering of photoelectron due to the higher concentration of gas as well as surface adsorbed species between the ceria film and analyzer cone. The catalyst was then heated from 300 to 700 K by 100 K increments in an ambient of 40 mTorr ethanol and 200 mTorr H2O, and the corresponding AP-XPS results for the C 1s, O 1s and Ce 4d regions are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37] Rodriguez et al studied WGS over Au/TiO 2 (110), and on the basis of experiments and theoretical calculations they concluded that the metalsupport interface is critical for the activation of water and the formation of a carboxyl intermediate which further decomposes into CO 2 and H 2 . 29 Ribeiro and co-workers elucidated the effect of the interface on water activation and determined that the WGS reaction rate scales linearly with the number of under-coordinated Au atoms, estimated from physical models of Au clusters and particle size measurements.…”
Section: Introductionmentioning
confidence: 99%
“…23,24,25,26,27 For example, experimental and theoretical studies for the CeO x /Cu and CeO x /TiO 2 systems have shown that at small coverages of ceria, the ceria nanoparticles favor a +3 oxidation state. 28,29,30,31 Furthermore, in an oxide-metal interface, in addition to the changes in the reducibility of the oxide, one can also observe a perturbation in the electronic properties of the metal. 32,33,34,35,36 Electronic perturbations can also occur after forming a carbide-metal interface.…”
Section: Introductionmentioning
confidence: 99%